2010
DOI: 10.1186/1742-2094-7-61
|View full text |Cite
|
Sign up to set email alerts
|

Distinct modulation of microglial amyloid β phagocytosis and migration by neuropeptidesi

Abstract: Microglial activation plays an integral role in the development and course of neurodegeneration. Although neuropeptides such as bradykinin (BK), somatostatin (SST), and endothelin (ET) are known to be important mediators of inflammation in the periphery, evidence of a similar function in brain is scarce. Using immunocytochemistry, we demonstrate the expression of receptors for BK (B1, B2 subtypes), ET (ETA, ETB subtypes) and SST (SST 2, 3, 4 subtypes) in primary microglia and microglial cell lines. Exposure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 44 publications
3
47
0
Order By: Relevance
“…Another interesting finding of the present study was the increased Aβ deposition in KOB2Aβ mice, suggesting that B2R activation may play an important role in Aβ degradation in vivo. Supporting our data, it was shown that the concentration-dependent stimulation of BV2 and N9 cell lines or primary microglial cells by BK or endothelin increased the phagocytosis of Aβ by these cells (Fleisher-Berkovich et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Another interesting finding of the present study was the increased Aβ deposition in KOB2Aβ mice, suggesting that B2R activation may play an important role in Aβ degradation in vivo. Supporting our data, it was shown that the concentration-dependent stimulation of BV2 and N9 cell lines or primary microglial cells by BK or endothelin increased the phagocytosis of Aβ by these cells (Fleisher-Berkovich et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…In all groups of cells, the levels of intracellular Aβ peaked at 3 h (Fig. 3B), consistent with previous results obtained using microglia [71,72]. By comparison, at 6 h, the intracellular Aβ levels were substantially lower, indicating that the rate of protein degradation far exceeded the rate of A) The gene expression levels of 6 proteins were analyzed by real-time PCR test.…”
Section: Pea15 Is Involved In Astrocyte-mediated Aβ Phagocytosissupporting
confidence: 89%
“…Another study showed that SST dose-dependently induces A β 1–42 phagocytosis in BV-2, N9, and rat primary microglial cells, supporting a protective role for SST in the development of AD by modulating microglial function [63]. However, this study showed no effect of SST either alone or in combination with A β on IDE or on neprilysin (another enzyme involved in A β degradation) expression in BV-2 and N9 cells [63]. The discrepancies may be due to the use in the second study of a much lower concentration of SST (100 nM) versus the 0.5–10  μ M concentrations used in the first study or also to differences in incubation times before protein assessment.…”
Section: Somatostatinmentioning
confidence: 97%
“…The receptors were functionally active, since SST-14 affected microglial protein phosphorylation and inhibited microglial proliferation induced by granulocyte macrophage colony-stimulating factor (GM-CSF) and IL-3 [62]. Immunoreactivity for sst2, sst3, and sst4 was later detected in BV-2, N9, and mouse primary microglial cells, and SST induced migration in BV-2 and N9 cells [63]. Activation of sst2, sst3, and sst4 in neonatal rat microglia inhibited LPS-induced PGE 2 production [150], suggesting an anti-inflammatory role for SST in microglial cells.…”
Section: Somatostatinmentioning
confidence: 99%